College Algebra (10th Edition)

Published by Pearson
ISBN 10: 0321979478
ISBN 13: 978-0-32197-947-6

Chapter 3 - Section 3.1 - Functions - 3.1 Assess Your Understanding: 77



Work Step by Step

We are given: $f(x)=3x+1$ and: $(f+g)(x)=6-\displaystyle \frac{1}{2}x$ Thus: $g(x)=(f+g)(x)-f(x)$ $g(x)=6-\displaystyle \frac{1}{2}x-3x-1$ $g(x)=5-\frac{7}{2}x$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.